تأثير نظم الحراثة ونوع السماد العضوي في نمو الباذنجان وإنتاجه - عمران, علي أمين (Latakia University Journal -Biological Sciences Series, 2014)
نفذ البحث خلال الموسم الزراعي 2012 في قرية كرتو التابعة لمنطقة الصفصافة جنوبي محافظة طرطوس. وقد تمّ فيه دراسة ثلاثة نظم للحراثة (1-حراثة سطحية20 - 0 سم، 2- حراثة متوسطة 30-0 سم ، 3- حراثة عميقة40-0 سم ) ومستوى واحد لثلاثة أنواع سمادية عضوية ( روث أبقار - زبل أغنام - زرق دواجن ) وتمّ دراسة بعض المؤشرات شملت: ارتفاع النبات، عدد الفروع الخضرية، وزن الثمرة، الوزن الرطب والجاف للنبات (الأوراق والسيقان)، الإنتاجية. تفوقت الحراثة العميقة معنوياً على الحراثة المتوسطة والسطحية في الصفات المدروسة وأعطت أعلى إنتاج إذ بلغ 12.5 كغ/م2 مقابل 11.5 كغ/م2 في الحراثة المتوسطة و10كغ/م2 في الحراثة السطحية. تبيّن تفوق معاملة التسميد بزرق الدواجن معنوياً على التسميد بسماد الأغنام والأبقار في الصفات المدروسة وبلغ إنتاجها 13كغ/م2 مقابل 11و10.5كغ/م2 لمعاملة سماد الأغنام والأبقار بالترتيب. وحققت معاملة الحراثة العميقة مع التسميد بسماد زرق الدواجن أفضل القيم إذ وصل إنتاج وحدة المساحة 14كغ/م2 . This research was carried out during 2012 in Karto village/Safsafe region/Tatrtous. Three kinds of tillage were experimented (tipper surface plough: 0-20cm, tipper medium plough: 0-30cm, and tipper deep plough: 0- 40cm) with three kinds of fertilizers: cow dung, sheep discharge, and chicken excrement. The study focused on several indicators which included: the plant height, number of green twigs, fruit average weight, wet and dry weight of leaves and stems, and plant productivity .In deep plough, the studied characteristics were significantly superior to those in the medium and surface plough, and gave the highest production 12.5kg/m2 versus 11.5kg/m2 in the medium tillage, and 10kg/m2 in the surface tillage. With regards to the studied characteristics, the chicken excrement was significantly more productive than cow dung and sheep discharge. Its production reached 13kg/m2 compared to 11 and 10.5kg/m2 for the treatment of sheep and cow manure respectively. The treatment of deep tillage fertilizing with chicken manure fertilizer achieved the best values; the production per unit area reached 14kg/ m2.